Leukocytoclastic Vasculitis as a Rare Dermatologic Extraintestinal Manifestation of Ulcerative Colitis in an Elderly Patient with Positive PR3-ANCA - Jacky Ng; David Zezoff; Hanadi Abou Dargham (Case Reports in Gastrointestinal Medicine)
Ulcerative colitis is an inflammatory bowel disease that in rare cases may develop extraintestinal manifestations. This case report aims to add to the limited clinical data on leukocytoclastic vasculitis and possible ANCA-associated vasculitis as rare cutaneous and rheumatologic extraintestinal manifestations of IBD, particularly in elderly patients. Our case involves a 79-year-old male with a history of mild-moderate ulcerative colitis on oral mesalamine 2.4 g daily and pyoderma gangrenosum who presented with recurrent bilateral polyarthralgia, joint swelling, diffuse lower extremity purpura, acute kidney injury, and scrotal rash. Autoimmune titers were significant for positive ANA and PR3-ANCA. Biopsy of purpuric lesions demonstrated findings suggestive of leukocytoclastic vasculitis. The patient was promptly treated with pulse-dose methylprednisolone for 3 days with rapid improvement of symptoms.